Altered Rb, p16, and p53 expression is specific for porocarcinoma relative to poroma. (3rd May 2019) - Zahn, Joseph; Chan, May P.; Wang, Grace; Patel, Rajiv M.; Andea, Aleodor A.; Bresler, Scott C.; Harms, Paul W.
Abstract: Background: Porocarcinomas are rare aggressive carcinomas that harbor tumor suppressor mutations and must be distinguished from benign entities such as poromas. Methods: To determine whether altered expression of these genes was diagnostically informative, we examined p53, Rb, and p16 staining patterns in 15 poromas and 16 porocarcinomas. Results: Poromas consistently displayed diffuse strong expression of Rb in all but one case that displayed focal loss (1/15, 7%), and no evidence of aberrancy in p53 or p16. Porocarcinomas displayed diffuse or focal loss of Rb expression in 9/16 (56%) cases, diffuse loss or overexpression of p53 in 8/15 (53%), and diffuse loss or overexpression of p16 in 6/14 (43%). Diffuse aberrancy in p53 and Rb expression correlated with tumor mutations in TP53 and RB1, respectively, whereas focal Rb loss was associated with wild type RB1 . Diffuse p16 overexpression correlated with Rb loss rather than CDKN2A mutation. For porocarcinomas with all three stains evaluable, 10/13 (77%) displayed aberrancy in at least one marker. Conclusions: Our findings suggest that altered p53, p16, and/or Rb expression is relatively specific to porocarcinoma in comparison with poroma. Technical limitations of this panel, including possible focal Rb loss, must be kept in mind, especially in limited samples.